IABSE-ADIAB: IAB job vacancy survey data linked to administrative data - Benjamin Lochner (Journal of Economics and Statistics, 2024)
The IABSE-ADIAB dataset provides the linkage between the most recent case of a hire from the IAB Job Vacancy Survey and the administrative data of the hired person. The data comprise the entire working history of persons who were identified as IAB Job Vacancy Survey hires from 2010 to 2020. The data are processed in a similar manner to the Sample of Integrated Employment Biographies of the IAB and can be linked to the survey data using the provided unique key variable.
Keywords: J23; J63; E24; 330; data linkage; German administrative microdata; IAB job vacancy survey; labour market data